Self-Managed Non-Pharmacological Interventions for Breast Cancer Survivors: Systematic Quality Appraisal and Content Analysis of Clinical Practice Guidelines - Tan, Jing-Yu (Benjamin); Zhai, Jianxia; Wang, Tao; Zhou, Hong-Juan; Zhao, Isabella; Liu, Xian-Liang (Frontiers in Oncology, 2022)
Background: A growing number of clinical practice guidelines (CPGs) regarding non-pharmacological interventions for breast cancer survivors are available. However, given the limitations in guideline development methodologies and inconsistent recommendations, it remains uncertain how best to design and implement non-pharmacological strategies to tailor interventions for breast cancer survivors with varied health conditions, healthcare needs, and preferences. Aim: To critically appraise and summarise available non-pharmacological interventions for symptom management and health promotion that can be self-managed by breast cancer survivors based on the recommendations of the CPGs. Methods: CPGs, which were published between January 2016 and September 2021 and described non-pharmacological interventions for breast cancer survivors, were systematically searched in six electronic databases, nine relevant guideline databases, and five cancer care society websites. The quality of the included CPGs was assessed by four evaluators using the Appraisal of Guidelines for REsearch and Evaluation, second edition tool. Content analysis was conducted to synthesise the characteristics of the non-pharmacological interventions recommended by the included CPGs, such as the intervention’s form, duration and frequency, level of evidence, grade of recommendation, and source of evidence. Results: A total of 14 CPGs were included. Among which, only five were appraised as high quality. The “range and purpose” domain had the highest standardized percentage (84.61%), while the domain of “applicability” had the lowest (51.04%). Five CPGs were rated "recommended," seven were "recommended with changes," and the other two were rated "not recommended". The content analysis findings summarised some commonly recommended self-managed non-pharmacological interventions in the 14 guidelines, including physical activity/exercise, meditation, hypnosis, yoga, music therapy, stress management, relaxation, massage and acupressure. Physical activity/exercise was the most frequently recommended approach to managing psychological and physical symptoms by the included guidelines. However, significant variations in the level of evidence and grade of recommendation were identified among the included CPGs. Conclusion: Recommendations for the self-managed non-pharmacological interventions were varied and limited among the 14 CPGs, and some were based on medium- and low-quality evidence. More rigorous methods are required to develop high-quality CPGs to guide clinicans in offering high-quality and tailored breast cancer survivorship care.